Automated Motion Detection Security System Notifier using Raspberry Pi with Telegram - Hazri I.M.; Rahman S.A.; Hussin F.S.; Mus’ab Sahrim; Wan Zakiah Wan Ismail; Irneza Ismail (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus